Great Expectations? Relation of Previous Experiences With Social Robots in Real Life or in the Media and Expectancies Based on Qualitative and Quantitative Assessment - Horstmann, Aike C.; Krämer, Nicole C. (Frontiers in Psychology, 2019)
Social robots, which mostly look and behave like humans, are often perceived as somehow alive and treated similar to humans, despite the fact that they are non-living electronic devices. Based on considerations of the uncertainty reduction theory, the question arises what expectancies regarding social robots people have and what sources they use to achieve these expectancies. To receive an in-depth understanding of people’s expectancies regarding social robots and particularly how these expectancies are influenced by people’s experiences with real robots but also with fictional robots from media, thirteen semi-structured interviews and a quantitative online study (n = 433) were conducted. Results indicate that people’s experiences with robots in the media lead to high expectations regarding the skills of robots, which in turn increase people’s general expectancies regarding social robots being part of the society as well as their personal lives. Furthermore, knowledge of negatively perceived fictional robots increases negative expectancies of robots becoming a threat to humans, while technical affinity reduces general robot anxiety.